The Perception of Teachers on the Integration of AI in English Language Teaching - Qonita Adlina Mardhiyya; Ayunda Retno Saptaningtyas; Shine Kayla Matswa Syifa; Viviana Lisma Lestari (Universitas Islam Negeri Palopo, 2025)
Artificial Intelligence (AI) is increasingly utilized in English Language Teaching (ELT) and is frequently recognized for its contribution to lesson preparation, developing resources, and improving the effectiveness of learning.However, a significant portion of the studies has concentrated on wider or student-oriented perspectives, leading to limited insights into how secondary educators in Indonesia perceive and implement AI in their daily teaching practices. Employing the Technological Pedagogical Content Knowledge (TPACK) framework along with a human-centered pedagogical approach, this descriptive qualitative research explores English teachers' views regarding the benefits, challenges, and consequences of incorporating AI into English Language Teaching (ELT). Semi-structured interviews were conducted with 4 English teachers from a senior high school and a vocational high school in South Tangerang, with the data being examined through thematic analysis. The results indicate that teachers find AI to be a helpful resource for generating ideas, planning lessons, tailoring content, and offering timely feedback, which leads to more efficient and innovative teaching strategies. However, there were also worries about students becoming too dependent on AI, issues of plagiarism, diminished critical thinking skills, and the disconnect between AI-created texts and the actual language proficiency of students. The research emphasizes the crucial part teachers play in providing emotional encouragement, inspiration, and moral guidance, highlighting that AI should be regarded as an assistant in education, not as a substitute for teachers. Despite its findings, this study is limited by a narrow sample size and a specific educational setting. In practical terms, the results indicate a need for structured training for educators, well-defined ethical standards, and thorough school regulations to facilitate the effective and responsible application of AI in classrooms focused on English language instruction.